Online Course Quality Assurance: Development of a Quality Checklist - Steven J. McGhan, MSEd; Christina M. Jackson, APR, EdD; Karen Premer, MSEd (Park University, 2015)
The University of Nebraska at Kearney's Online Course Checklist is the main instrument for assessing the quality of online courses at UNK. A number of issues were faced when developing and deploying this quality assurance checklist at a small four-year university. The process including development, implementation, and revision is discussed along with the need for faculty buy-in. Special considerations included how to assess the quality of an online course while ensuring academic freedom in accordance with a union contract. The purpose of this case study is to provide a roadmap for institutions that are developing an instrument of their own.